Occurrence of tuberculosis cases in Crato, Ceará, from 2002 to 2011: a spatial analisys of specific standards - Mayrla Lima Pinto; Talina Carla da Silva; Lidiane Cristina Félix Gomes; Maria Rita Bertolozzi; Lourdes Milagros Mendoza Villavicencio; Kleane Maria da Fonseca Araújo Azevedo; Tânia Maria Ribeiro Monteiro de Figueiredo (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVE: to analyze the spatial distribution of tuberculosis in Crato, Ceará, Brazil, from 2002 to 2011, aiming to check for a point pattern. METHODS: This is an ecological, temporal trend and hybrid design study, with a quantitative approach. A total of 261 cases of tuberculosis were geo-referenced and 20 (7.1%) were considered as losses due to the lack of address. The profile of patients in 10 years of study was in accordance with the following pattern: men aged between 20 and 59 years, with low schooling, affected by the pulmonary form of tuberculosis and who were cured from the disease. RESULTS: The analysis of the spatial distribution of tuberculosis points out that in the period of study, new cases of the disease were not distributed on a regular basis, indicating a clustered spatial pattern, confirmed by the L-function. The map with the density of new cases estimated by the Kernel method showed that the "hot" areas are more concentrated in the vicinity of the central urban area. CONCLUSION: The study allowed pointing out areas of higher and lower concentration of tuberculosis, identifying the spatial pattern, but it also recognized that the disease has not reached all of the population groups with the same intensity. Those who were most vulnerable were the ones who lived in regions with higher population densities, precarious living conditions, and with intense flow of people.